avec la collaboration de Dominique Beyer, Olivier Callot, Rémi Dalongeville, Jacqueline Gachet, Jean-Jacques Glassner, Pierre Lombard, Jean Marcillet-Jaubert, Marielle Pic, Christian Robin, Maurice Sznycer, Failaka: Fouilles françaises 1984-1985 - Calvet, Yves (1986)
französischer und englischer Text nebeneinander; setzt 48:2035 fort